Learning Experiences of Teachers Attending Online Webinars - Sodais Tarusan; Genesis Naparan; Gilbert Celesio (Multidisciplinary Journal of School Education, 2022)
The shift from actual seminars to the internet-mediated webinar format has changed how teachers access opportunities for continuous learning. Attending webinars has also become necessary as teachers look for alternative ways to further develop their knowledge. The purpose of this study was to explore the learning experiences of the teachers who attend webinars. This study used Meriam’s case study research method; intensive, holistic description; and analysis of a bounded phenomenon, such as a program, institution, person, process, or social unit. The study was conducted in the elementary schools of Sultan Naga Dimaporo West District, Division of Lanao del Norte, Philippines for the 2020–2021 school year. It was found that most teachers participated in webinars about teaching strategies, content knowledge, the teaching profession, and general knowledge related to the pandemic. It was also revealed that these teachers are expected to gain relevant knowledge and skills applicable to “the new normal.” The teachers shared their experiences in acquiring knowledge, skills, and emotional content in their actual participation in the webinars during the pandemic. The teacher’s purpose of attending  webinars is to gain understanding of the topic to improve the quality of teaching. Thus, the webinar presents an opportunity to expand teacher training programs amid the pandemic.